Imaginary female journeys The woman and the place in selected tales from the book "One Thousand and One Nights" - قدّاح رؤى (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The research is based on the study of the problematic relationship between women and the place as revealed in some tales and imaginary female journeys selected from "One Thousand and One Nights". And by comparing the feminine journeys and the two most prominent male journeys in the book: Sinbad and Blogia, it shows the inability of imagination to build a feminine journey comparable to them. The research concluded several results, including: the consolidation of tales of the male perception of the image of the female traitor, and the association of female journeys with magic, betrayal and jinn, and ended with regression and submission to the male cultural system and its formats and institutions, and the culture’s punishment of rebels against the place by killing, raping, or selling in the slave market, and glorifying stillness in women’s lives as their protector from the dangers that lurk in foreign spaces, and glorifying travel in men’s lives as a way of knowledge, gratitude, glory and heroism.